القضية العرقية والأمن المجتمعي في رواندا - بو جدري, فيصل (University of Eloued جامعة الوادي, 2021)
تحاول هذه الورقة أن تتوجه بالبحث صوب إحدى أهم مناطق إفريقيا اضطرابا وصناعة للأحداث، وهي منطقة البحيرات الكبرى، وبالضبط ستبحث جانبا من القضية الإثنية في دولة رواندا. وهي إذ تقوم بذلك تلتزم بالتقيد قدر المستطاع بمقتضيات منهجية علم الإيثنولوجيا الذي يهتم بدراسة الإثنيات والعرقيات من جهة، ومنهجية التحليل في الدراسات التوسيعية لمفهوم الأمن من جهة أخرى وذلك من خلال البحث في العلاقة بين جماعات مختلفة عرقيا وتعيش في مجتمع واحد، وعلاقة النظام السياسي بها، وتأثير تلك العلاقة متعددة المستويات - سواء كانت من طبيعة تعاونية أو تنازعية- على أمن واستقرار الأفراد والجماعات أولا ثم على الدولة. كما سيكون هدف الورقة في ذلك هو الوصول إلى فهم جيد لسيرورة الجماعات والثقافات داخل المجتمعات التعددية ومعرفة مهددات الأمن فيها بالتركيز على مقاربة الأمن المجتمعي والمعضلة الأمنية الإثنية منها بالأساس. The current research paper tries to shed light on one of the most turbulent and teeming regions of Africa, which is the Great Lakes region. It examines an aspect of the ethnic question in Rwanda. In doing so, it is committed to comply as much as possible with the requirements of ethnology method, which is particularly concerned with the study of ethnicities and ethnics on the one hand, and the analysis methodology in the broadening studies of the security concept on the other hand. To achieve the latter an investigation has been conducted to clarify the relation between different societal ethnic groups, their relation with the political system, and the impact of that multi-levels relation whether of a cooperative or conflictual nature, on the security and the stability of individuals and groups at first and then on the state. This research paper aims to reach a better understanding of the process of groups and cultures within pluralistic societies, and to know the security threats in them by focusing mainly on the societal security approach and the ethnic security dilemma.
مقال
Keywords: الكلمات المفتاحية: رواندا، الأمن المجتمعي، الجماعة العرقية، الإبادة الجماعية، المعضلة الأمنية الإثنية. ; Keywords: Rwanda - societal security - ethnic group - genocide - the ethnic security dilemma.